Growth velocity of extremely low birth weight preterms at Groote Schuur Hospital nursery - Lango, M O (Division of Neonatology, 2015)
To describe the growth velocity of extremely low birth weight babies seen at Groote Schuur Hospital nursery and to compare this to growth velocities of similar babies in published literature.